Device‐Measured Physical Activity As a Predictor of Disability in Mobility‐Limited Older Adults. Issue 10 (11th August 2017) - Mankowski, Robert T.; Anton, Stephen D.; Axtell, Robert; Chen, Shyh‐Huei; Fielding, Roger A.; Glynn, Nancy W.; Hsu, Fang‐Chi; King, Abby C.; Layne, Andrew S.; Leeuwenburgh, Christiaan; Manini, Todd M.; Marsh, Anthony P.; et al.
Abstract : Objectives: To examine associations between objectively measured physical activity (PA) and incidence of major mobility disability (MMD) and persistent MMD (PMMD) in older adults in the Lifestyle Interventions and Independence for Elders (LIFE) Study. Design: Prospective cohort of individuals aged 65 and older undergoing structured PA intervention or health education. Setting: The LIFE Study was a multicenter (eight sites) randomized controlled trial designed to compare the efficacy of a long‐term structured PA intervention with that of a health education (HE) program in reducing the incidence of MMD in mobility‐limited older adults. Participants: LIFE Study participants (n = 1, 590) had a mean age±standard deviation of 78.9 ± 5.2, low levels of PA, and measured mobility‐relevant functional impairment at baseline. Measurements: Activity data were collected using hip‐worn 7‐day accelerometers at baseline and 6, 12, and 24 months after randomization to test for associations with incident MMD and PMMD (≥2 consecutive instances of MMD). Results: At baseline, every 30 minutes spent being sedentary (<100 accelerometry counts per minute) was associated with higher rate of subsequent MMD (10%) and PMMD (11%) events. Every 500 steps taken was associated with lower rate of MMD (15%) and PMMD (18%). Similar associations were observed when fitting accelerometry‐based PA as a time‐dependent variable. Conclusion: Accelerometry‐based PA levels were strongly associated with MMD and PMMD events in older adults with limited mobility. These results support the importance of daily PA and lower amounts of sedentary time levels in this population and suggest that accelerometry may be a useful tool for assessing risk of mobility disability.